Conservation of freshwater biodiversity in key areas of the Colombian Amazon. Issue 2 (7th September 2015) - Portocarrero‐Aya, Marcela; Cowx, Ian G.
Abstract: Little has been done to identify key conservation areas in the Amazonian freshwater ecosystems of Colombia. This research constitutes the first attempt to systematically identify important conservation areas in the freshwater ecosystems of the South of the Colombian Amazonian Trapezium. This effort considered not only fine filter targets (species) as central elements of decision making, but coarse filter targets (habitats), ecosystem services and social benefits, and threats. Owing to the complexity of the study area, a multi‐criteria assessment constituted a good approach to tackle the issues affecting a complex ecological, cultural, social, economic and political territory. Five sites stood out and were considered important as areas for targeted management: the Tarapoto Lakes System, Yahuarcaca Lakes System, Loreto‐Yacu River, and Mocagua Island (Colombia) and Caballo Cocha Lake (Peru). Biodiversity conservation initiatives as well as livelihood improvement projects are currently in motion in the area aiming to find a balance between resource use and local development. Copyright © 2015 John Wiley & Sons, Ltd.